Angioneurotic edema of metastatic breast cancer patient associated with letrozole - Yasemin Bakkal Temi; Ali Murat Sedef (Journal of Oncological Sciences)
Breast cancer is the most frequent cancer in women leading to a Significant morbidity and mortality. The majority of breast malignancies are hormone responsive. We present a case of letrozole-associated angioneurotic edema in a 62-year-old woman with metastatic breast cancer. Angioneurotic edema is the insidious side effect of letrozole. Clinical suspicion is the key to the early diagnosis.